Absensi SISTEM MONITORING KEHADIRAN SISWA MENGGUNAKAN MIKROKONTROLLER BERBASIS WEB - Taufik Kurnialensya; Puput Candra Saputra (LPPM Universitas Abdurrab, 2023)
An attendance information system, used to record a person's presence, is used as a reference for proof someone is present at an activity. Ease of information and the validity of information is a fundamental requirements in making attendance reports. The use of manual attendance has several drawbacks, including the lack of direct and fast transfer of information to other parties, and inaccurate data validity. Technology that can be applied in creating an attendance information system using a microcontroller and a website, in designing an attendance system using the Arduino UNO R3 microcontroller board as a controller, and ESP32-CAM as a camera for taking pictures. Sending data using a student card in the form of an RFID card. Overall, from the results of testing the attendance information tool and system, it can work well, namely, it can retrieve data from student cards and take pictures of students' faces and can be displayed on web pages.